The Verb Of The Languages Of Malaysing Sanggau A Sosiomorfosemantic Study - Netti Yuniarti; Sri Kusnita (International Journal of Multi Discipline Science, 2018)
This study focused on the discussion of Sanggau Malay verbs related to the formation of verbs or morphological processes, the meaning of verbs related to the user community, and with the context behind the emergence of verbs in the language. This research uses descriptive qualitative method with sociomorphosemantic approach. The data in this research is informant speech reflecting the formation of verbs, meanings, and verb functions in Sanggau Malay language. The data source in this research is Sanggau Malay language which is spoken by Sanggau Malay society. Data collection techniques in this study using techniques of observation, recording, and interviews. Based on the results and discussionfaund that the verbs in the Sanggau Malay seen from the morphology process divided into two, namely the establishment of affix verb derived verbs and verbs duplicate. The verb consists of prefixes, suffixes, and confixes which have intentional, active, and passive meanings. The formation of duplicated verbs is a reduplicated type of affixtion. The use of Sanggau Malay verbs in relation to the language user community exists in situations or family contexts, joking contexts, and circumstances contexts.